The Influence of Service Quality on the Level of Customer Satisfaction at Bank BTPN Makassar Branch Office - Putri Adilah (Journal AGENCY, 2024)
This research is a type of quantitative research with the aim of determining the effect of service quality on the level of customer satisfaction at Bank BTPN Makassar Branch Office. The population in this study was 1,500 customers. The sampling technique in the research used the Slovin technique with simple random sampling with a sample size of 43 customers. This sample was taken from Bank BTPN Makassar Branch Office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the statistical package for the social science (SPSS) version 29 application regarding the influence of service quality on the level of customer satisfaction at Bank BTPN Makassar Branch Office which was discussed previously, the author draws conclusions from the research results, namely quality service has a positive and significant effect on the level of customer satisfaction and the coefficient of determination of 88% can illustrate that customer satisfaction is influenced by service quality while the remaining 12% represents shortcomings and limitations of the research model carried out. Service quality must be maintained and further improved because it can be seen from the research results that the existing service quality is quite strong.